Som e vida após a lata: construção de instrumentos musicais com material alternativo - Garcia, Daniele Munhoz [UNESP] (2013)
This paper aimed to verify the interference of the construction of musical instruments with alternative material as a solution to students’ belief in the inability to practice music, and in the idea that the act of playing is conditioned on acquisition of a musical instrument, changing what they think about playing instruments and empowering this way their belief of their own capacity. The results were obtained through field research with interviews, observation workshops of musical instruments with alternative material and analysis of documents about the subject, and the triangulation of these sources by the qualitative method. It was concluded that to obtain a positive result it is necessary to have a pre-consciousness or at least not to install a limiting thought in relation to musical practice, in first instance an easy and successful experience with tools simple to perform, as well as social network that encourages and time as an important factor for changing. It was verified that four workshops presented results confirming the hypothesis, two in a more significant, which supports the construction of musical instruments with alternative material as a possible tool for teaching music geared to the needs of students, as a facilitator of musical practice to them, and as an opportunity for personal development beyond the music